2016
DOI: 10.1186/s12885-016-2619-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment MRI minimum apparent diffusion coefficient value is a potential prognostic imaging biomarker in cervical cancer patients treated with definitive chemoradiation

Abstract: BackgroundDiffusion Weighted (DW) Magnetic Resonance Imaging (MRI) has been studed in several cancers including cervical cancer. This study was designed to investigate the association of DW-MRI parameters with baseline clinical features and clinical outcomes (local regional control (LRC), disease free survival (DFS) and disease specific survival (DSS)) in cervical cancer patients treated with definitive chemoradiation.Methods This was a retrospective study approved by an institutional review board that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The latter was insufficient at some point of tumour growth resulting in critical shortage of oxygen and nutrients and consecutive development of necrosis. This may indicate a poorer prognosis as Marconi et al recently showed in women with advanced-stage cervical cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter was insufficient at some point of tumour growth resulting in critical shortage of oxygen and nutrients and consecutive development of necrosis. This may indicate a poorer prognosis as Marconi et al recently showed in women with advanced-stage cervical cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to high diffusion coefficient in necrotic tissue, it has been suggested that ADC values can be used to assess hypoxia [ 113 ]. Several studies have indeed reported an association between high pre-treatment ADC and poor outcome in cervical cancer [ 114 , 115 ]. However, the opposite relationship has also been found [ 116 , 117 ], probably reflecting an aggressive tumor phenotype with low ADC caused by high cellularity.…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, low mean pre-treatment ADC has been associated with good outcome [49] , whereas the opposite relationship has also been reported [50] . Other studies found a relation of parameters derived from histograms of ADC distribution within the GTV and treatment response [49] , [51] , [52] . Perfusion-related parameters have been less studied.…”
Section: Potential Benefits Of Dwi For Rtmentioning
confidence: 91%